Knowledge economy and gender inequality. (1st December 2022) - Nathan, Dev; Kelkar, Govind; Govindnathan, Pallavi
Abstract: The paper analyzes how gender inequality is created in the knowledge economy through forms of exclusion of women from certain areas of knowledge, and the simultaneous higher social valuation of men's monopolized knowledge as against women's knowledge in the commons. Gendered knowledge inequality has consequences for other forms of inequality, such as in status, ownership of property, distribution of labor and even consumption. Besides explicit exclusions, the definition and responsibility of women as bearers and nurturers of children and for domestic care work becomes a severe constraint in their ability to access and use forms of monopolized knowledge.